Laser Drop on Demand Micro Joining − Analytic Process Model to Quantify Braze Absorptance and Cumulative Energy Balance. Issue 12 (19th August 2018) - Stein, Stefan; Schaumberger, Kerstin; Frick, Thomas; Roth, Stephan; Schmidt, Michael
Abstract : Laser drop on demand joining is used for high temperature applications particularly tailored for temperature stable joining of electrode structures of piezo actuators with copper wires. The process is developed, since the generated joints are able to withstand the temperatures occurring during aluminum die‐casting, which is a proposed technology to integrate sensor or actuator functionalities into structural aluminum components. The process is based on melting a spherical copper based braze preform (CuSn12) with a liquidus temperature of 989.85 °C. The preform is induced into a capillary and subsequently molten by a laser pulse. After reaching liquidus temperature, the droplet is ejected from the capillary by inert gas overpressure and wets the surface of the electrode structure and the copper wire, where it results in a firm joint after solidification. In order to be able to estimate the cumulative energy balance during the melting and detachment of the braze material, an analytical model is established in the scope of this work, enabling for the first time to indirectly quantify the braze spheres reflectivity as well as its loss of thermal energy due to convection, radiation, and conduction in situ. The analytic model is verified by experiments. The insights gained, may be applied to investigate other laser based metal joining processes like welding, as it is almost impossible to quantify reflectivity or thermal energy losses directly during the welding process. Abstract : An analytical model is introduced to describe the laser drop on demand joining process, which is based on the melting of a spherical braze preform by a laser pulse to generate thermally stable joints. The analytical model enables a quantification of absorptance and thermal energy loss, indicating a significantly improved efficiency if high pulse powers are chosen to melt the braze preform.